IMPLEMENTATION OF INQUIRY BASED-PHYSICS LEARNING TO IMPROVE STUDENTS’ SCIENTIFIC PROCESS SKILLS ON MOMENTUM AND IMPULS IN GRADE X OF SENIOR HIGH SCHOOL - ALFAZRIYAH, OKTAVIANA (Inovasi Pendidikan Fisika, 2018)
The goals of this research was to describe the practicality of inquiry based-physics learning to improve students’ scientific process skills in term of teacher’s activities treatment and students’ activities, and to describe the effectiveness in term of the scientific process skills improvement, classical mastery and students’ responses. This research was pre experimental research by using one group pretest-posttest design. The sample of this research was determined by ensuring that the population was distributed normally and had homogenous ability, so it obtained grade XI MIA 1 and X MIA 2 of SMAN 1 Sooko as the samples. Inquiry based-physics learning could be implemented and successfully increased students’ scientific process skills in very good category. Students’ activity was categorized as good. Students’ learning achievement scope of knowledge could obtained classical mastery by 93,06 %. Students’ response of inquiry based-phisics learning model had very good criteria in both class. Based on that result, it showed that implementation of inquiry based-physics learning model could improve students’ scientific process skills. Keywords: inquiry, scientific process skills, momentum and impuls.